Glass composition for ink, glass with ink layer, and ion exchange strengthened glass with ink layer
By using a pre-exchanged ink glass composition in automotive chemical tempered glass to form a sodium ion enrichment layer and performing K ion exchange, the problem that good chemical reinforcement in the printing area in the prior art is solved, and the glass is improved Overall strength and performance reduce warping and deformation caused by uneven stress.
Patent Information
- Application Number
- CN202411590499.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The existing automotive chemical tempered laminated glass cannot achieve good chemical reinforcement in the printing area, resulting in limited functional integration, weakening of strength and increased risk of lobes. At the same time, the existing technology has no exchange and non-printing areas in the printing area during the ion exchange reinforcement process. There are exchanged asymmetric stress problems, which affect the overall performance of the glass.
Using a glass composition for ink that performs Na ion exchange in advance, a sodium ion enrichment layer is formed on the glass surface by printing the ink layer, and K ion exchange is performed after high temperature sintering to establish a Na-K concentration difference to achieve ion exchange strengthening and improve Glass strength and overall performance in the printing area.
It realizes the consideration of ink printing and ion exchange strengthening in chemical tempered glass, improves the glass strength of the printing area, reduces warping and deformation caused by uneven stress in non-printing areas and printing areas, and meets the performance requirements of automotive laminated glass .
Smart Images

Figure CN119263627A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a glass composition for ink, glass with an ink layer and ion exchange strengthened glass with an ink layer, belonging to the technical field of laminated glass preparation. Background Art
[0002] The appearance design of current chemically tempered laminated glass for automobiles is restricted. The outer glass bears all the printed decorative layers and printed functional layers, that is, the black border, trademark and silver paste are all printed on the inner surface of the outer glass, while the inner glass is not printed. On the one hand, this method makes all the inner printed patterns visible, and the functional integration of the laminated glass is adversely affected. For example, the embedded copper foil, electrodes, circuits, etc. cannot be effectively shielded, and dimming, display, heating and other functions are difficult to integrate on the chemically tempered laminated glass. On the other hand, too many decorative layers further weaken the strength of the outer glass, resulting in an increased risk of cracking.
[0003] Moreover, since the printed shielding layer will form a dense glass layer after high-temperature sintering, which hinders ion exchange strengthening, the method of first printing and sintering and then chemically tempering will result in no strengthening effect in the printed area.
[0004] The existing technology of printing and sintering the decorative layer and then tempering, that is, printing and high-temperature sintering the shielding layer, and then chemically strengthening, on the one hand, the printing ink after tempering will fade, thereby contaminating the ion exchange salt tank and causing the salt bath to fail, and on the other hand, since there is no exchange in the printing area and there is exchange in the non-printing area, asymmetric stress is generated on the two surfaces of the glass, causing the printed area of the glass to deform during the chemical tempering process. However, the method of first chemically strengthening, then printing high-temperature ink and sintering, will cause the chemical tempering compressive stress to disappear due to the high sintering temperature.
[0005] CN113924278A, CN117597232A and the like disclose some chemical tempered printing methods, which are to first print porous ink, and the ink layer after sintering will form a porous structure. After ion exchange, the printing area has a certain strengthening effect. Then, in order to solve the light leakage problem at the pores, an additional organic shielding layer needs to be coated on the printing area or the organic shielding layer is integrated on the surface of the intermediate film, and the pores are filled in the process of sandwiching and gluing sheets. On the one hand, these methods put forward higher requirements on porous ink materials, and there are great difficulties in controlling the high-temperature sintering process to form a planar uniform porous structure during implementation. In addition, the use of organic layer coating is prone to cause color difference with the original porous ink layer, and the durability is difficult to meet the requirements of automotive-grade decorative layers. The method of integrating the coating layer in the intermediate film can only be used for printing on the third side, and cannot meet the printing requirements of the fourth side (the inner surface of the chemically tempered inner sheet).
[0006] No matter before or after chemical strengthening, it is impossible to print the automotive high temperature sintering shielding layer, resulting in that the existing automotive chemically tempered glass is all non-printed glass.
[0007] Therefore, how to solve the problem that the printed area of chemically strengthened glass cannot achieve good chemical strengthening is one of the problems to be solved urgently in this field. Summary of the invention
[0008] In order to solve the above technical problems, the object of the present invention is to provide a glass composition for ink, wherein the glass printing ink made of the glass composition for ink can allow K ions to pass through after sintering, so as to achieve ion exchange strengthening of the glass.
[0009] Another object of the present invention is to provide a glass printing ink made from the above-mentioned glass composition for ink.
[0010] The present invention also aims to provide glass with an ink layer and a method for preparing the same. By pre-exchanging Na ions on the glass, then printing ink and performing K ion exchange, ion exchange strengthening of the printed area can be achieved.
[0011] The present invention also aims to provide an ion-exchange strengthened glass with an ink layer prepared by using the glass with an ink layer and a preparation method thereof.
[0012] Another object of the present invention is to provide a laminated glass for a vehicle using the ion-exchange strengthened glass with an ink layer.
[0013] To achieve the above-mentioned object, the present invention first provides a glass composition for ink, wherein, calculated by the mass of oxides, the glass composition for ink comprises the following components in percentage by mass: 15%-30% SiO2, 25%-50% Bi2O3, 10%-20% Cr2O3, 5%-15% CuO, 1%-10% ZnO, 3%-15% Al2O3, 1%-10% Na2O, 0.5%-10% K2O, 0.5%-6% ZrO2, 0-8% MnO, 0.1%-1% TiO2, and 0.1%-1% Fe2O3.
[0014] The glass composition for ink provided by the present invention can be made into glass powder by the existing glass powder preparation method, and then used as a raw material to make printing ink. After printing and sintering, a glass sintered body will be formed, and the glass sintered body can be ion exchanged.
[0015] According to a specific embodiment of the present invention, preferably, based on the mass of oxides, the glass composition for ink comprises the following components in percentage by mass: 20%-25% SiO2, 30%-40% Bi2O3, 15%-20% Cr2O3, 7%-11% CuO, 3%-10% ZnO, 5%-10% Al2O3, 3%-8% Na2O, 2%-6% K2O, 0.5%-3% ZrO2, 0-5% MnO, 0.1%-1% TiO2, and 0.1%-1% Fe2O3.
[0016] Compared with ordinary automotive glass ink, the glass composition for ink provided by the present invention is a high-temperature sintering ink composition, which can bring the following technical effects: 1. The content of SiO2 and Al2O3 is significantly increased, which can form a [SiO4] and [AlO4] network structure that is beneficial to ion exchange as much as possible, and at the same time improve the matching of the glass performance of the ink layer and the performance of the aluminosilicate substrate glass; 2. The content of Na2O and K2O is appropriately increased, which can increase the alkali metal oxide content of the ink body without affecting the glass structure and sintering performance of the ink layer, increase the diffusion concentration difference effect, and improve the ion exchange efficiency.
[0017] The present invention further provides a glass with an ink layer, wherein the glass with an ink layer comprises a glass substrate and an ink layer, wherein the ink layer is formed by glass printing ink and the above-mentioned ink-glass composition on a partial area of the surface of the glass substrate;
[0018] Wherein, a sodium ion-enriched layer is formed on the surface of the glass substrate;
[0019] Calculated by the mass of Na2O, the sodium ion content in the sodium ion-enriched layer is ≥15wt%, preferably 15wt%-25wt%.
[0020] The chemical tempering process of aluminosilicate glass is an ion exchange process based on the concentration diffusion effect. The high-concentration K ions in the salt bath used in the ion exchange exchange the Na ions in the glass to form stress. The glass composition contains a certain amount of Na2O and K2O, and the proportion of Na2O must be significantly higher than the proportion of K2O (generally, in conventional high-aluminum glass compositions, the Na2O content is not less than 1.5 times the K2O content) to form a sufficient Na-K concentration difference relative to the K salt bath, providing the required diffusion power to achieve smooth exchange.
[0021] The present invention forms a sodium ion enriched layer on the surface of the glass, and the sodium ion enriched layer is located below the surface of the glass, so that the sodium ion concentration on the surface of the glass can be increased. The sodium ion concentration of the sodium ion enriched layer is higher than that of the ink layer, thereby forming a sodium ion concentration difference between the surface of the glass and the ink layer. Moreover, the surface of the glass with the ink layer has no compressive stress.
[0022] The raw material of the glass powder of the ink is generally a low-melting-point glass system of bismuth salts, and its bismuth oxide content is at least 25%. The glass structure with bismuth oxygen bonds as the main body has relatively strict restrictions on alkali metal raw materials. Generally, the Na2O content does not exceed 5%, the K2O content does not exceed 2%, and the total alkali metal oxide content is less than 1 / 3 of that of aluminosilicate glass. If the percentage of alkali metal oxides is further increased, the thermal stability and expansion coefficient of the bismuth salt glass system will be significantly affected, resulting in a series of problems such as mismatch with the glass matrix, glass cracks caused by high-temperature sintering, and insufficient ink adhesion. Therefore, it is difficult to provide the required concentration difference conditions on the surface of the ink layer, and ion exchange is difficult. Silicon oxide is not the main component of the glass body of the ink layer, and its content is generally 10-25%. The aluminum oxide content of the glass body of the ink layer is less than 2%. The number of [SiO4] tetrahedrons and [AlO4] tetrahedrons that provide exchange channels in the glass structure of the ink layer is limited, which further limits the diffusion and movement of Na ions and K ions in the ink layer.
[0023] During the sintering process of the ink layer of the present invention, Na ions will preferentially diffuse into the ink layer in large quantities (the content of Na ions in the ink layer is lower than that in the glass substrate), and can fill the [SiO4] tetrahedron and [AlO4] tetrahedron in the glass body of the ink layer as much as possible, while increasing the content of Na ions, thereby establishing ion exchange conditions for K ion exchange strengthening. When K ion exchange strengthening is performed on the glass with the ink layer provided by the present invention, K ions can be smoothly exchanged to the ink layer, and diffusion conditions can be established on the surface of the ink layer and the glass substrate, so that the glass surface can also generate K-Na exchange stress, so that K ions can enter the interior of the glass substrate, and ion strengthening of the glass substrate area covered by the ink layer is achieved.
[0024] According to a specific embodiment of the present invention, preferably, the potassium ion content in the sodium ion-enriched layer is ≤5wt% based on the mass of K2O. By controlling the potassium ion content of the sodium ion-enriched layer at a relatively low level, it is beneficial to facilitate the ion exchange between the K ions entering the ink layer and the glass substrate during the K ion exchange strengthening process.
[0025] According to a specific embodiment of the present invention, preferably, the thickness of the ink layer is 5-30 μm, more preferably 5-15 μm. The thickness of the ink layer refers to the thickness of the ink layer after sintering. The lower the thickness of the ink layer, the smaller the weakening effect on ion exchange, but the lower the ink shielding ability, which may cause defects such as light leakage and color difference; the thicker the ink layer, the more significant the hindrance to ion exchange. Controlling the thickness of the ink layer within the above range can avoid a strong weakening effect on ion exchange while taking into account the shielding ability of the ink layer.
[0026] According to a specific embodiment of the present invention, preferably, the area ratio of the ink layer on the surface of the glass substrate is ≤25%.
[0027] According to a specific embodiment of the present invention, preferably, based on the mass of oxides, the glass substrate comprises the following components in percentage by mass: 50%-70% SiO2, 4%-22% Al2O3, 8%-18% Na2O, 0-5% Li2O, 0-1% CaO, 1%-5% MgO, 3%-10% K2O, 0-0.08% Fe2O3, 0-2% ZrO2, and 0-5% B2O3. More preferably, the glass substrate comprises the following components in percentage by mass: 55%-65% SiO2, 8%-15% Al2O3, 10%-15% Na2O, 0-2% Li2O, 0-0.1% CaO, 3%-5% MgO, 5%-9% K2O, 0-0.08% Fe2O3, 1-2% ZrO2, and 1-5% B2O3.
[0028] According to a specific embodiment of the present invention, preferably, the glass with the ink layer has a thickness of 0.7-1.2 mm.
[0029] According to a specific embodiment of the present invention, preferably, the bending rupture strength of the printed area of the glass with the ink layer is not less than 100 MPa, and the bending strength of the printed area of the glass with the ink layer is not less than 30% of the bending strength of the non-printed area of the glass with the ink layer. By controlling the bending rupture strength value of the printed area and the ratio between the bending rupture strength of the printed area and the bending strength of the non-printed area, the glass warping due to uneven stress on the upper and lower surfaces of the printed area can be prevented.
[0030] According to a specific embodiment of the present invention, the glass composition for ink of the present invention can be made into glass printing ink, and then an ink layer is formed on a partial area of the surface of the glass substrate; that is, the present invention can also provide a glass printing ink, which contains the above-mentioned glass composition for ink.
[0031] According to a specific embodiment of the present invention, preferably, in the above-mentioned glass printing ink, the composition of the ink comprises 60%-75% of structural components and 25%-40% of auxiliary components by mass percentage; the structural component is the above-mentioned glass composition for ink.
[0032] According to a specific embodiment of the present invention, preferably, in the above glass printing ink, the auxiliary components include, by mass percentage, 80%-90% of an organic solvent, 0.5%-1.5% of an auxiliary agent, and 8%-15% of a binder.
[0033] The glass printing ink provided by the present invention can be prepared by a common preparation method of glass printing ink.
[0034] According to a specific embodiment of the present invention, preferably, in terms of mass percentage, the auxiliary components include 80%-90% of organic solvent, 0.5%-1.5% of auxiliary agent, and 8%-15% of binder. Among them, the auxiliary components used can be auxiliary components commonly used in ink layers, which will volatilize during the sintering process. Specifically, the organic solvent can be selected from one or more of pineneol, turpentine, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and hydrogenated castor oil; the auxiliary agent includes a leveling agent and a dispersant. Specifically, the leveling agent can be selected from one or more of polyacrylic resin BYK350, 352, and 354, and the dispersant can be selected from one or more of TEGO Dispers 652, DA302N, and DISPER BYK-115 / 160 / 161 / 162 / 164 / 165; the binder can be selected from one or more of resin and ethyl cellulose.
[0035] The present invention also provides a method for preparing the glass with an ink layer, which comprises the following steps:
[0036] Performing Na ion exchange on the surface of the glass substrate to form a sodium ion enriched layer on the surface of the glass substrate;
[0037] The glass with the ink layer is obtained by printing ink containing a glass composition for ink on the surface of a glass substrate formed with a sodium ion-enriched layer, and sintering the ink layer to form an ink layer.
[0038] According to a specific embodiment of the present invention, preferably, in the above-mentioned method for preparing glass with ink layer, the Na ion exchange is carried out using a NaNO3 salt bath with a purity of ≥95wt%. If the concentration of the NaNO3 salt bath is lower than 95%, Na will be enriched on the surface of the glass. + Insufficient content, Na transferred to the ink layer during the ink sintering process + Reduce, lower the second exchange K+ The effect of penetrating the ink layer causes the stress and strength of the printed area to be too different from that of the non-printed area, affecting the effect of preventing the glass from warping.
[0039] According to a specific embodiment of the present invention, preferably, in the method for preparing the glass with an ink layer, the temperature of the Na ion exchange is 350° C.-430° C., and the time is 30-180 min.
[0040] According to a specific embodiment of the present invention, preferably, in the method for preparing the glass with ink layer, the sintering temperature is 500-700° C. The sintering process can be completed by a separate heating and cooling process, or the sintering can be completed while the glass is bent and formed.
[0041] According to a specific embodiment of the present invention, preferably, in the above-mentioned method for preparing glass with an ink layer, after the Na ion exchange, the flat warping change of the glass substrate is ≤0.1%. The technical solution provided by the present invention can control the warping change of the glass substrate and can minimize the glass warping deformation caused by uneven stress.
[0042] According to a specific embodiment of the present invention, preferably, in the method for preparing the glass with an ink layer, the printing is performed by screen printing and / or inkjet printing.
[0043] According to a specific embodiment of the present invention, in the method for preparing the glass with an ink layer, before ion exchange, the original glass can be cut, broken and ground to form it into a desired shape, which can be done according to conventional methods in the art.
[0044] The glass with an ink layer provided by the present invention does not require secondary coating or secondary printing. During the K ion exchange process, the glass in the printed coverage area can also undergo ion exchange with the molten salt to form stress, thereby improving the glass strength in the printed area and reducing the glass warping deformation caused by uneven stress in the non-printed area and the printed area, thereby achieving chemically tempered glass that meets the requirements of ink printing and ion exchange strengthening at the same time.
[0045] The present invention also provides an ion exchange strengthened glass with an ink layer, wherein the ion exchange strengthened glass with an ink layer is obtained by subjecting the above-mentioned glass with an ink layer to K ion exchange strengthening.
[0046] According to a specific embodiment of the present invention, preferably, the surface compressive stress of the non-printing area of the ion-exchange strengthened glass with the ink layer is 500-900 MPa.
[0047] According to a specific embodiment of the present invention, preferably, the stress layer depth of the non-printing area of the ion-exchange strengthened glass with the ink layer is 30-50 μm.
[0048] According to a specific embodiment of the present invention, preferably, the flexural strength of the non-printing area of the ion-exchange strengthened glass with the ink layer is 300-600 MPa.
[0049] According to a specific embodiment of the present invention, preferably, the bending strength of the printed area of the ion-exchange strengthened glass with the ink layer is 100-200 MPa.
[0050] The present invention also provides a method for preparing the above-mentioned ion exchange strengthened glass with an ink layer, which comprises the following steps:
[0051] The glass with the ink layer is subjected to K ion exchange strengthening to obtain the ion exchange strengthened glass with the ink layer.
[0052] According to a specific embodiment of the present invention, preferably, in the method for preparing the ion exchange strengthened glass with an ink layer, the K ion exchange strengthening is carried out using a KNO3 salt bath with a purity of ≥95%wt.
[0053] According to a specific embodiment of the present invention, preferably, in the method for preparing the ion-exchange strengthened glass with an ink layer, the temperature of the K ion exchange is 380° C.-450° C., and the time is 120-480 min.
[0054] According to a specific embodiment of the present invention, preferably, in the method for preparing the ion-exchange strengthened glass with an ink layer, after the K ion exchange, the warpage change of the glass is ≤0.3%.
[0055] The present invention also provides a laminated glass for a vehicle, comprising an outer glass sheet and an inner glass sheet, wherein the inner glass sheet is the above-mentioned ion exchange strengthened glass with an ink layer.
[0056] According to a specific embodiment of the present invention, preferably, the ink layer is on the third surface or the fourth surface of the automotive laminated glass.
[0057] According to a specific embodiment of the present invention, preferably, the thickness of the outer glass is 2.6-5.0 mm.
[0058] According to a specific embodiment of the present invention, preferably, the outer glass is heat-strengthened glass or chemically-strengthened glass.
[0059] According to a specific embodiment of the present invention, preferably, the automotive laminated glass further comprises a film disposed between the outer glass and the inner glass. More preferably, the film is selected from one or a combination of two or more of EVA film, PVB film, SGP film, and PU film.
[0060] The technical solution provided by the present invention can achieve chemical tempering of the printed area of chemically strengthened glass for automobiles, and the obtained glass has high strength. At the same time, the glass warping deformation caused by the uneven stress between the glass in the non-printing area and the printed area is small, and the requirements of ink printing and ion exchange strengthening can be taken into account. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is the test result of Na element distribution on the interface of glass after Na+ exchange. DETAILED DESCRIPTION
[0062] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0063] definition :
[0064] Printing area: The area of the glass surface covered by the ink layer.
[0065] Non-printing area: The area on the glass surface not covered by the ink layer.
[0066] Examples 1-3
[0067] Embodiments 1-3 respectively provide a laminated glass for a vehicle, which is prepared by the following steps:
[0068] 1. Produce the outer glass according to the existing process, including cutting, grinding, printing and molding heat strengthening steps;
[0069] 2. Cut the inner glass into shape and place the cut glass in a salt bath with a NaNO3 purity of ≥95wt% and exchange at 350-430℃ for 30-180min. The test results of the interface Na element distribution of the glass after the Na+ exchange in this step are as follows: Figure 1 As shown;
[0070] 3. Printing an ink layer on the inner glass sheet using an ink containing a glass composition for ink as a shielding layer, and subjecting the inner glass sheet to high temperature treatment at a temperature between the glass transition point and the softening point (500°C-700°C) and then cooling and annealing. During the high temperature treatment, the shielding layer is sintered at high temperature, and the inner glass sheet is bent and formed into a shape matching the outer glass sheet, thereby obtaining the inner glass sheet with an ink layer;
[0071] 4. Perform ion exchange strengthening on the inner glass of step 3, place the inner glass with the ink layer in a salt bath with KNO3 purity ≥ 95wt%, and exchange at a temperature of 380-450°C for 120-480min;
[0072] 5. Lay the outer glass of step 1 and the inner glass of step 4 together and pressurize them to obtain the laminated glass for automobile;
[0073] The lamination process includes: cutting the middle layer according to the glass contour, stacking the outer glass, middle layer, and inner glass in order in a dust-free environment, aligning the overlap of the peripheral edges, and sequentially passing through two heating and two rolling processes (rolling temperature is 120°C, rolling pressure is 0.3MPa), exhausting the gas in the middle layer and initially bonding the middle layer to the glass;
[0074] The high-pressure process includes: placing the assembled glass in an autoclave, increasing the temperature and pressure and maintaining the temperature and pressure for a period of time, with the maximum temperature being 140°C, the maximum pressure being 1MPa, and the temperature and pressure maintaining time being 30 minutes. After the end, the temperature is slowly reduced and the pressure is released.
[0075] The glass composition for ink used in Examples 1-3 (structural components of ink) has the following composition: 5.86% Na2O, 0.04% MgO, 4.16% Al2O3, 16.6% SiO2, 3.43% K2O, 0.08% CaO, 0.12% TiO2, 19.12% Cr2O3, 5.41% MnO, 0.29% Fe2O3, 10.22% CuO, 1.42% ZnO, 4.35% ZrO2, 28.9% Bi2O3. The auxiliary components in the ink can be selected as needed, and these auxiliary components will volatilize during the sintering process and will not remain in the final ink layer.
[0076] The thickness of the outer glass used in Examples 1-3 is 3.5 mm, specifically, it is conventional soda-lime glass that has been physically tempered. The thickness of the inner glass is 1.1 mm, the glass size is 120×50 mm, the inner glass printing size (i.e., the size of the ink layer) is 120×10 mm, and the composition of the inner glass is: 59.8% SiO2, 14.3% Al2O3, 11.8% Na2O, 0.01% CaO, 4.85% MgO, 6.72% K2O, 0.02% Fe2O3, 1.5% ZrO2, and 1% B2O3.
[0077] Comparative Example 1
[0078] This comparative example provides a laminated glass for a vehicle, which is prepared by the following steps:
[0079] 1. Produce the outer glass according to the existing process, including cutting, grinding, printing and molding heat strengthening steps;
[0080] 2. Cut the shape of the inner glass;
[0081] 3. Use common ink to print an ink layer on the inner glass as a shielding layer, and perform high-temperature treatment at a temperature between the glass transition point and the softening point (500°C-700°C) and then cool and anneal. During the high-temperature treatment, the shielding layer completes high-temperature sintering, and at the same time, the inner glass is bent into a shape that matches the outer glass, thereby obtaining an inner glass with an ink layer;
[0082] 4. Perform ion exchange strengthening on the inner glass of step 3, place the inner glass with the ink layer in a salt bath with KNO3 purity ≥ 95wt%, and exchange at a temperature of 380-450°C for 120-480min;
[0083] 5. The outer glass of step 1 and the inner glass of step 4 are combined and high-pressured (in the same manner as in Examples 1-3) to obtain the laminated glass.
[0084] The structural components of the ordinary ink used in this comparative example 1 are: 20.2% SiO2, 39.2% Bi2O3, 18.9% Cr2O3, 8.87% CuO, 4.97% ZnO, 1.68% Al2O3, 3.17% Na2O, 0.14% K2O, 0.52% ZrO2, 2.31% TiO2, and 0.04% Fe2O3; the auxiliary components in the ink can be selected as needed, and these auxiliary components will volatilize during the sintering process and will not remain in the final ink layer.
[0085] Comparative Example 2
[0086] This comparative example provides a laminated glass for a vehicle, which is prepared by the following steps:
[0087] 1. Produce the outer glass according to the existing process, including cutting, grinding, printing and molding heat strengthening steps;
[0088] 2. Cut the inner glass into shape, and place the cut glass in a salt bath with a NaNO3 purity of ≥95wt%, and exchange at a temperature of 350-430℃ for 30-180min;
[0089] 3. Print an ink layer on the inner glass sheet using ordinary ink (same as in comparative example 1) as a shielding layer, and perform high-temperature treatment at a temperature between the glass transition point and the softening point (500° C.-700° C.) and then cool and anneal. During the high-temperature treatment, the shielding layer is sintered at high temperature, and the inner glass sheet is bent and formed into a shape matching the outer glass sheet, thereby obtaining an inner glass sheet with an ink layer;
[0090] 4. Perform ion exchange strengthening on the inner glass of step 3, place the inner glass with the ink layer in a salt bath with KNO3 purity ≥ 95wt%, and exchange at a temperature of 380-450°C for 120-480min;
[0091] 5. The outer glass of step 1 and the inner glass of step 4 are combined and high-pressured (in the same manner as in Examples 1-3) to obtain the laminated glass.
[0092] Comparative Example 3
[0093] This comparative example provides a laminated glass for a vehicle, which is prepared by the following steps:
[0094] 1. Produce the outer glass according to the existing process, including cutting, grinding, printing and molding heat strengthening steps;
[0095] 2. Cut the shape of the inner glass;
[0096] 3. Print an ink layer on the inner glass using the ink of Examples 1-3 as a shielding layer, and perform high-temperature treatment at a temperature between the glass transition point and the softening point (500° C.-700° C.) and then cool and anneal. During the high-temperature treatment, the shielding layer is sintered at high temperature, and the inner glass is bent into a shape matching the outer glass, thereby obtaining an inner glass with an ink layer.
[0097] 4. Perform ion exchange strengthening on the inner glass of step 3, place the inner glass with the ink layer in a salt bath with KNO3 purity ≥ 95wt%, and exchange at a temperature of 380-450°C for 120-480min;
[0098] 5. The outer glass of step 1 and the inner glass of step 4 are combined and high-pressured (in the same manner as in Example 1) to obtain the laminated glass.
[0099] Blank comparison (inner film):
[0100] This comparative example provides a laminated glass for a vehicle, which is prepared by the following steps:
[0101] 1. Produce the outer glass according to the existing process, including cutting, grinding, printing and molding heat strengthening steps;
[0102] 2. Cut the inner glass into shape, place it in a salt bath with KNO3 purity ≥ 95wt%, and exchange it at 380-450℃ for 120-480min;
[0103] 3. The outer glass of step 1 and the inner glass of step 4 are combined and pressurized (in the same manner as in Example 1) to obtain the automotive laminated glass.
[0104] The specific process parameters of the embodiments and comparative examples are shown in Table 1:
[0105] Table 1
[0106]
[0107]
[0108] In Table 1, the ion exchange parameters are the type and concentration of the salt bath, the temperature of the ion exchange, and the time of the ion exchange.
[0109] The elemental composition of the ink layer (ie, shielding layer) after high-temperature sintering in step 3 of Examples 1-2 and Comparative Example 3 is shown in Table 2.
[0110] Table 2
[0111]
[0112] The performance test of the glass obtained from Examples 1-3, Comparative Examples 1-3 and the blank comparative example was carried out, and the specific test method is as follows:
[0113] Bending Strength :
[0114] The conventional three-point bending method (GB / T 34171-2017 Three-point bending method for testing the bending properties of thin and ultra-thin glass) was used to test the bending strength of the glass. Specifically, the inner glass printed surface was kept facing downward and stretched. The bending strength of the outer glass in step 1, the bending strength of the inner glass in step 4, and the bending strength of the laminated glass in step 5 were tested respectively. The lower span was 100 mm, the loading speed was 5 mm / min, and the loading was continued until the glass broke. σ = 3P × L / (2b × h 2 ) was used to calculate the three-point bending strength, where σ is the bending strength (MPa), P is the loading rupture force (N), L is the lower span (mm), b is the sample width (mm), and h is the sample glass thickness (mm).
[0115] Flat plate warpage :
[0116] The flatness test method is used to test the warpage change of the inner glass in step 4 before and after the second ion exchange strengthening. Specifically, the sample is placed flat on the flatness table, and a sheet feeler gauge is used to measure the maximum height of the glass edge from the platform, and the height is divided by the diagonal length of the glass as the warpage percentage.
[0117] The test results are shown in Tables 3 and 4.
[0118] Table 3
[0119]
[0120] Note: The bending strength of the inner glass of Examples 1-3 and Comparative Examples 1-3 represents the bending strength of the printed area, and for the sake of clarity, they are listed separately in Table 3.
[0121] Table 4
[0122]
[0123] From the test results in Table 3 and Table 4, we can see that:
[0124] Although the bending strength of the inner glass produced by the ink material and preparation method of the present invention is lower than that of the non-printed blank glass, the overall bending strength of the laminated glass does not decrease significantly after it is formed into a laminated glass with the outer glass, and the chemical strengthening warping caused by the obstruction of ion exchange in the printed area is also within an acceptable range.
[0125] However, the inner glass printing area of Comparative Examples 1-3 is not significantly strengthened, and the bending strength of the inner glass is too low, resulting in a significant decrease in the bending strength of the interlayer, and a significant increase in chemical strengthening warpage, which makes it difficult to meet the manufacturing requirements and performance requirements of automotive laminated glass, among which:
[0126] Comparative Example 1 is a prior art process;
[0127] Comparative Example 2 uses a common shielding layer. Although the first ion exchange has been performed, the ink layer is difficult to provide an ion exchange channel. The Na+ on the glass surface is difficult to diffuse into the ink layer during the sintering process. The K+ in the salt bath during the second ion exchange process is also difficult to replace the Na+ in the shielding layer and exchange to the glass surface.
[0128] Although comparative example 3 uses an exchangeable shielding layer material, since it has not undergone pre-exchange, it is difficult for the shielding layer to provide sufficient Na+ for exchange with the salt bath K+ after sintering. The ion diffusion concentration difference is insufficient, and it is also difficult for K+ to be exchanged from the ink layer to the glass surface to generate compressive stress and strength.
Claims
1. A glass composition for ink, characterized in that: Calculated by the mass of oxides, the glass composition for ink comprises the following components in percentage by mass: 15%-30% SiO2, 25%-50% Bi2O3, 10%-20% Cr2O3, 5%-15% CuO, 1%-10% ZnO, 3%-15% Al2O3, 1%-10% Na2O, 0.5%-10% K2O, 0.5%-6% ZrO2, 0-8% MnO, 0.1%-1% TiO2, and 0.1%-1% Fe2O3.
2. The glass composition for ink according to claim 1, characterized in that: Calculated by the mass of oxides, the glass composition for ink comprises the following components in percentage by mass: 20%-25% SiO2, 30%-40% Bi2O3, 15%-20% Cr2O3, 7%-11% CuO, 3%-10% ZnO, 5%-10% Al2O3, 3%-8% Na2O, 2%-6% K2O, 0.5%-3% ZrO2, 0-5% MnO, 0.1%-1% TiO2, and 0.1%-1% Fe2O3.
3. A glass with an ink layer, characterized in that: The glass with ink layer comprises a glass substrate and an ink layer, wherein the ink layer is formed by the glass composition for ink according to claim 1 or 2 on a partial area of the surface of the glass substrate; Wherein, a sodium ion-enriched layer is formed on the surface of the glass substrate; Calculated by the mass of Na2O, the sodium ion content in the sodium ion-enriched layer is ≥15wt%.
4. The glass with ink layer according to claim 3, characterized in that: Calculated by the mass of K2O, the potassium ion content in the sodium ion enriched layer is ≤5wt%.
5. The glass with ink layer according to claim 3, characterized in that: The ink layer has a thickness of 5-30 μm.
6. The glass with ink layer according to claim 3, characterized in that: Calculated by the mass of oxide, the glass substrate comprises the following components in mass percentage: 50%-70% SiO2, 4%-22% Al2O3, 8%-18% Na2O, 0-5% Li2O, 0-1% CaO, 1%-5% MgO, 3%-10% K2O, 0-0.08% Fe2O3, 0-2% ZrO2, 0-5% B2O3.
7. The glass with ink layer according to claim 3, characterized in that: The thickness of the glass with the ink layer is 0.7-1.2 mm.
8. The glass with ink layer according to claim 3, characterized in that: The bending fracture strength of the printed area of the glass with the ink layer is not less than 100 MPa, and the bending strength of the printed area of the glass with the ink layer is not less than 30% of the bending strength of the non-printed area of the glass with the ink layer.
9. The method for preparing glass with ink layer according to any one of claims 3 to 8, characterized in that: The following steps are involved: Performing Na ion exchange on the surface of the glass substrate to form a sodium ion enriched layer on the surface of the glass substrate; The glass with the ink layer is obtained by printing ink containing a glass composition for ink on the surface of a glass substrate formed with a sodium ion-enriched layer, and sintering the ink layer to form an ink layer.
10. The method for preparing glass with an ink layer according to claim 9, characterized in that: The Na ion exchange is carried out using a NaNO3 salt bath with a purity of ≥95wt%.
11. The method for preparing glass with an ink layer according to claim 9, characterized in that: After the Na ion exchange, the flat plate warpage change of the glass substrate is ≤0.1%.
12. An ion exchange strengthened glass with an ink layer, characterized in that: The ion exchange strengthened glass with an ink layer is obtained by strengthening the glass with an ink layer according to any one of claims 3 to 8 through K ion exchange.
13. The ion-exchange tempered glass with an ink layer according to claim 12, characterized in that: The surface compressive stress of the non-printing area of the ion-exchange strengthened glass with the ink layer is 500-900 MPa.
14. The ion-exchange tempered glass with an ink layer according to claim 12, characterized in that: The stress layer depth of the non-printing area of the ion-exchange strengthened glass with the ink layer is 30-50 μm.
15. The ion-exchange tempered glass with an ink layer according to claim 12, characterized in that: The flexural strength of the non-printing area of the ion-exchange strengthened glass with the ink layer is 300-600 MPa.
16. The ion-exchange strengthened glass with an ink layer according to claim 12, characterized in that: The bending strength of the printed area of the ion-exchange strengthened glass with the ink layer is 100-200 MPa.
17. The method for preparing the ion exchange strengthened glass with ink layer according to any one of claims 12 to 16, characterized in that: The following steps are involved: The glass with an ink layer according to any one of claims 3 to 8 is subjected to K ion exchange strengthening to obtain the ion exchange strengthened glass with an ink layer.
18. The method for preparing ion-exchange strengthened glass with ink layer according to claim 17, characterized in that: After the K ion exchange, the warpage change of the glass is ≤0.3%.
19. A laminated glass for a vehicle, comprising an outer glass sheet and an inner glass sheet, characterized in that: The inner glass is the ion-exchange strengthened glass with an ink layer as described in any one of claims 12 to 16.
Citation Information
Patent Citations
Environmentally-friendly low-transparency type absolute black alumina silicate glass
CN103102070A
Glass powder, ink and chemically strengthened glass
CN108147673A
Glass ceramic cover plate, preparation method, repairing and fingerprint resisting method and electronic equipment
CN115477473A
Glass and preparation method thereof, glass piece and preparation method thereof, and electronic equipment
CN115818982A
Glass frit, glass composition, cooking appliance having glass composition, and method of forming glass composition
US20190092680A1